Environmentally relevant mixture of S-metolachlor and its two metabolites affects thyroid metabolism in zebrafish embryos - Rozmánková, Eliška; Pípal, Marek; Bláhová, Lucie; Njattuvetty Chandran, Naveen; Morin, Bénédicte; Gonzalez, Patrice; Bláha, Luděk (Aquatic toxicology (Amsterdam, Netherlands), 2020)
Herbicides and their metabolites are often detected in water bodies where they may cause adverse effects to non-target organisms. Their effects at environmentally relevant concentrations are often unclear, especially concerning mixtures of pesticides. This study thus investigated the impacts of one of the most used herbicides: S-metolachlor and its two metabolites, metolachlor oxanilic acid (MOA) and metolachlor ethanesulfonic acid (MESA) on the development of zebrafish embryos (Danio rerio). Embryos were exposed to the individual substances and their environmentally relevant mixture until 120 hpf (hours post-fertilization). The focus was set on sublethal endpoints such as malformations, hatching success, length of fish larvae, spontaneous movements, heart rate and locomotion. Moreover, expression levels of eight genes linked to the thyroid system disruption, oxidative stress defense, mitochondrial metabolism, regulation of cell cycle and retinoic acid (RA) signaling pathway were analyzed. Exposure to S-metolachlor (1 μg/L) and the pesticide mixture (1 μg/L of each substance) significantly reduced spontaneous tail movements of 21 hpf embryos. Few rare developmental malformations were observed, but only in larvae exposed to more than 100 μg/L of individual substances (craniofacial deformation, non-inflated gas bladder, yolk sac malabsorption) and to 30 μg/L of each substance in the pesticide mixture (spine deformation). No effect on hatching success, length of larvae, heart rate or larvae locomotion were found. Strong responses were detected at the molecular level including induction of p53 gene regulating the cell cycle (the pesticide mixture - 1 μg/L of each substance; MESA 30 μg/L; and MOA 100 μg/L), as induction of cyp26a1 gene encoding cytochrome P450 (pesticide mixture - 1 μg/L of each substance). Genes implicated in the thyroid system regulation (dio2, thra, thrb) were all overexpressed by the environmentally relevant concentrations of the pesticide mixture (1 μg/L of each substance) and MESA metabolite (1 μg/L). Zebrafish thyroid system disruption was revealed by the overexpressed genes, as well as by some related developmental malformations (mainly gas bladder and yolk sac abnormalities), and reduced spontaneous tail movements. Thus, the thyroid system disruption represents a likely hypothesis behind the effects caused by the low environmental concentrations of S-metolachlor, its two metabolites and their mixture.
Keywords: Embryonic Development; embryo nesavčí; Embryo, Nonmammalian; Sublethal effects; Embryotoxicity; Drug Synergism; Thyroid Gland; acetamidy; chemické látky znečišťující vodu; Zebrafish embryo; Metabolite; Acetamides; synergismus léků; herbicidy; Water Pollutants, Chemical; zvířata; Zebrafish; štítná žláza; dánio pruhované; Pesticide mixture; embryonální vývoj; larva; Larva; Herbicides; Environmental concentration; Animals